Evaluasi Usability dan Perbaikan Desain Website Dinas Pendidikan Kota Malang menggunakan Metode Heuristic Evaluation dengan Prinsip Usability G-Quality - Hilyah Nadhirah; Niken Hendrakusma Wardani; Komang Candra Brata (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2019)
As a form of implementing e-government and to improve the quality services, Department of Education of Malang uses their official website as media for news publications and documentation of activities related to education in Malang. In addition, the website of the Department of Education of Malang also provides an online complaint feature that used by users to send complaints if they experience or know of law violations related to education in Malang. However, according to preliminary observations by looking at the user interface of the Department of Education of Malang website, it was found that usability problems were still found such as not offer a home menu to make users easier to return into the main page. Therefore, to find usability problems more specifically, we need to do usability evaluation. In this study, usability evaluation was carried out using a heuristic evaluation method with the principle of usability g-quality which is an extension of the Nielsen heuristic principle that was adjusted for e-government website. The evaluation involving four usability expert evaluators resulted in 35 usability problems. Of the 35 problems there are 33 interface design problems whose recommendations for improvement are realized in the form of a prototype. From the follow-up evaluation on the repair prototype, it was found that only four usability problems were still found from a total of 33 problems. It states that 88% of usability issues related to user interface design on The Department of Education of Malang website have been resolved and only 12% of the remaining problems but with a lower severity rating than the first evaluation.